Pengaruh partisipasi anggaran dan akuntansi pertanggungjawaban terhadap kinerja pegawai pada badan pengelola keuangan dan aset daerah kota balikpapan - Beby Natalya; Dwi Risma Deviyanti; Annisa Kusumawardani (Faculty of Economics and Business Mulawarman University, 2016)
This study aims to know the influence of budgetary participation, and responsibility accounting to employee performance in Finance and Asset Management Body Area of the City of Balikpapan. Data collection is done by giving 40 copies of the questionnaire, but only 37 questionnaire which the data could be analyzed and processed. The questionnaire distributed to the respondents who was work in Finance and Asset Management Body Area of the City of Balikpapan. The research analysis data used SmartPLS. The result of this research showed that budgetary participation has significant positive impact influence to employee performance, and responsibility accounting has significant positive impact influence to employee performance. Keyword: Budgetary Participation, responsibility accounting, employee performance